2015
DOI: 10.1074/jbc.m114.619098
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-related Receptor β Reduces the Subnuclear Mobility of Estrogen Receptor α and Suppresses Estrogen-dependent Cellular Function

Abstract: Background:The role of orphan nuclear receptor ERR␤ in estrogen-related pathophysiology is poorly understood. Results: ERR␤ repressed the transactivity of ER␣ and proliferation of MCF-7 breast carcinoma cells through reduction of the intranuclear mobility of ER␣. Conclusion: ERR␤ affects ER␣ dynamics and function. Significance: Regulation of ERR␤ will provide a potential therapeutic approach for estrogen-related cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 68 publications
1
35
0
Order By: Relevance
“…Prior studies have evaluated the subcellular localization of untagged and epitope-tagged ERRβ splice variants in breast cancer and other cell lines, and have consistently shown that exogenous ERRβsf is a nuclear protein [26, 38], which we also observe for the endogenous splice variant in MDA-MB-231 and HCC1806 cells. However, there are discrepancies in the reported subcellular localization of exogenous ERRβ2.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Prior studies have evaluated the subcellular localization of untagged and epitope-tagged ERRβ splice variants in breast cancer and other cell lines, and have consistently shown that exogenous ERRβsf is a nuclear protein [26, 38], which we also observe for the endogenous splice variant in MDA-MB-231 and HCC1806 cells. However, there are discrepancies in the reported subcellular localization of exogenous ERRβ2.…”
Section: Discussionmentioning
confidence: 55%
“…High levels of total ESRRB mRNA in primary breast tumors are associated with a reduction in cells in S phase and increased expression of estrogen receptor beta (ERβ) [37]. In exogenous expression studies, ERRβsf interacts with ER, alters the intranuclear localization of ER, and suppresses ER-mediated gene transcription in MCF7 cells [38]. Exogenous expression of ERRβ “long form” (a synonym for ERRβ2 used by some) in MCF7 cells leads to apoptosis and also shows an interaction with ER that is attenuated upon exposure to estradiol [39].…”
Section: Resultsmentioning
confidence: 99%
“…Intranuclear dynamics are complex, affected by binding interactions, the presence of monomers vs dimers, flow, and inhomogeneity in space . Imaging studies of GFP‐tagged steroid hormone receptors, including the GR, mineralocorticoid receptor, estrogen receptor, and the androgen receptor have shown changes in intranuclear dynamics affected by a number of factors, such as ligand availability, transcriptional activity, and proteasomal activity . An earlier study of TRβ1 intranuclear mobility by FRAP noted that overexpression of SRC‐1, N‐CoR1, and HDAC did not affect TRβ1's intranuclear mobility; however, when factors retaining unliganded TRβ1 in the nucleus were studied, findings pointed towards a role of N‐CoR1 and RXR in maintaining the receptor in the nucleus .…”
Section: Discussionmentioning
confidence: 99%
“…ESRRB (estrogen-related receptor beta) encodes a protein similar to the estrogen receptor and is believed to have an inhibitory effect on estrogen signaling 27 . Mutations in this gene have also been associated with hearing impairment and dental decay 35 .…”
Section: Discussionmentioning
confidence: 99%